Community Influences on Female Genital Mutilation/Cutting: A Comparison of Four Francophone West African Countries. Issue 1 (27th February 2020) - Hayford, Sarah R.; Garver, Sarah; Soura, Abdramane B.; Cheong, Yuk Fai; Grose, Rose Grace; Yount, Kathryn M.
Abstract: Despite long‐term efforts to encourage abandonment of female genital mutilation/cutting (FGMC), the practice remains widespread globally. FGMC is situated in specific social and historical contexts, and both prevalence and rates of decline vary widely across practicing countries. However, cross‐national comparative research on the determinants of FGMC is sparse. This paper adds to the limited body of rigorous, theoretically grounded quantitative studies of FGMC and takes a step toward advancing cross‐national comparative research. We apply an integrated theoretical framework that brings together norms‐based and gender‐based explanations of community‐level influences on FGMC. We test this framework in four francophone West African countries, drawing on comparable nationally representative data from the Demographic and Health Surveys in Burkina Faso (2010), Côte d'Ivoire (2011–2012), Guinea (2012), and Mali (2012–2013). Results show that community‐level FGMC norms and community‐level gendered opportunities are associated with girls' risk of FGMC, but that the direct and moderating associations vary qualitatively across countries. Our findings highlight the contribution of context‐specific social and institutional processes to the decline or persistence of FGMC.